The determinants of users' intention to adopt telehealth: health belief, perceived value and self-determination perspectives - Yuen, Kum Fai (2023)
Telehealth is an effective and promising mode of healthcare delivery. It is crucial for society to understand the determinants of user adoption of telehealth to realize its benefits. This research investigates and analyzes the factors that impact the adoption of telehealth services from the users' perspective. The study integrates three theoretical frameworks, namely, Health Belief Model, Perceived Value Theory, and the Self-Determination Theory, to provide a comprehensive understanding of the determinants of telehealth adoption. Using an online survey conducted in Singapore, the study collected 500 responses for data analysis. The findings indicate that perceived threat, cues to action, and perceived relatedness directly affect perceived value, while self-efficacy, perceived relatedness, and perceived autonomy have a significant direct impact on emotion. Additionally, users' perceived value of telehealth services has a direct and indirect positive influence on their intention to adopt telehealth services through emotions. The study offers practical implications for healthcare organizations, policymakers, and media management teams to encourage the adoption of telehealth services by integrating various psychological and health concerns of users that impact their adoption behavior.